Three Selected Edible Crops of the Genus Momordica as Potential Sources of Phytochemicals: Biochemical, Nutritional, and Medicinal Values - Muronga, Mashudu; Quispe, Cristina; Tshikhudo, Phumudzo P.; Msagati, Titus A. M; Mudau, Fhatuwani N.; Martorell, Miquel; Salehi, Bahare; Abdull Razis, Ahmad Faizal; Sunusi, Usman; Kamal, Ramla Muhammad; Sharifi-Rad, Javad (Frontiers in Pharmacology, 2021)
Momordica species (Family Cucurbitaceae) are cultivated throughout the world for their edible fruits, leaves, shoots and seeds. Among the species of the genus Momordica, there are three selected species that are used as vegetable, and also for medicinal purposes inter alia Momordica charantia L. (Bitter melon), Momordica foetida Schumach. (Bitter cucumber) and Momordica balsamina L. (African pumpkin). The three species are reputed to possess anti-diabetic, anti-microbial, anthelmintic bioactivity, abortifacient, anti-bacterial, anti-viral, and also play chemo-preventive functions as they are rich in vitamins as well as both primary and secondary metabolites which possess anti-microbial activities. The fruits and leaves of Momordica species consist of nutritional composition rich in primary metabolites; energy releasing biomolecules, proteins, fibers, minerals (calcium, iron, magnesium, zinc), β-carotene, foliate and ascorbic acid. The extracts from Momordica species are used for the treatment of a variety of diseases and ailments. Several studies have suggested that Momordica species extracts can lower blood sugar and treat diabetes mellitus due to its hypoglycemic properties. The crop can also be used to treat other diseases including diarrhea, bleeding gums, piles and hemorrhoids; respiratory problems, leukemia, melanoma, liver cancer, skin infections, and solid sarcomas.